Impact of bioresorbable scaffold use on procedural features compared with new-generation drug-eluting stents - Çakal, Beytullah (Kartal Koşuyolu High Specialization Training and Research Hospital, 2020)
Introduction: Although bioresorbable scaffolds (BRS) are considered a new paradigm in stent technology, operators are often discouraged from implanting BRS because of increased strut thickness, reduced radial force, requirement for pre- and postdilatation of the lesions, and concerns about the risk of stent thrombosis. We compared procedure and fluoroscopy duration, cumulative radiation dose, and contrast agent volume among patients undergoing BRS or drug-eluting stent (DES) implantation.Patients and Methods: One hundred thirty-four patients with a total of 165 coronary lesions, including 64 patients (78 lesions) with BRS and 70 patients (87 lesions) with DES, were selected. Clinical and procedural characteristics and angiographic features were calculated. Procedure and fluoroscopy time, volume of contrast medium, and cumulative radiation dose (Gy) were compared.Results: The number of predilated and postdilated lesions was higher in the BRS group than in the DES group, although baseline lesion morphologies were similar. Stent diameters were comparable between the two groups. Larger postdilatation balloon sizes were chosen in the BRS group. Mean procedure time (45.4 ± 16.1 minutes vs. 38.3 ± 15.1 minutes; p= 0.010), volume of contrast medium (207.7 ± 80.7 mL vs. 154.7 ± 74.6 mL; p= 0.001), fluoroscopy duration (15.9 ± 6.6 minutes vs. 13.1 ± 6.6 minutes; p= 0.014), and radiation dose (1.80 ± 1.08 Gy vs. 1.44 ± 0.91 Gy, p= 0.037) were significantly higher in the BRS group than in the DES group.Conclusion: BRS implantation leads to prolonged fluoroscopy, longer procedure duration, greater contrast volume, and higher radiation exposure compared with DES procedures.

Giriş: Artmış strut kalınlığı, azalmış stentin açılma kuvveti, stent takılmadan önce ve sonrasında balon yapma ihtiyacı, stent trombozu riskinde artış gibi birçok faktör operatörleri yenilikçi bir teknoloji olarak sunulan eriyebilen stentlerin (ES) kullanılmasında endişeye itmiştir. Bu çalışmada ES ile ilaç salınımlı stent (İSS)kullanılan hastalardaki işlem süresi ve floroskopi zamanı, opak miktarı ve radyasyon dozu karşılaştırılması hedeflenmiştir. Hastalar ve Yöntem: Çalışmada koroner arter hastalığı tanısı alan 134 hastadaki 165 lezyon ele alınmış olup,bunlardan ES takılan 64 hastadaki 78 lezyon ile İSS takılan 70 hastadaki 87 lezyon dahil edilmiştir. İşlemle ilgili, klinik ve anjiyografik özellikler her grup için hesaplanmıştır. Her iki gruptaki prosedür ve floroskopizamanı, kontrast miktarı ve toplam radyasyon dozu (Gy) karşılaştırılmıştır. Bulgular: Başlangıç lezyon özellikleri her iki grupta benzer saptanmasına rağmen balon ile pre- ve postdilatasyon anlamlı olarak ES takılanlarda daha yüksek saptandı. Stent çapları iki grupta da benzer iken ES grubunda postdilatasyon için daha yüksek çaplı balonlar tercih edildi. Ortalama işlem süresi (sırasıyla 45.4 ±16.1 dakika ve 38.3 ± 15.1 dakika, p= 0.01), kontrast volümü (sırasıyla 207.7 ± 80.7 mL ve 154.7 ± 74.6 mL;p= 0.001), floroskopi zamanı (sırasıyla 15.9 ± 6.6 dakika ve 13.1 ± 6.6 dakika, p= 0.014), radyasyon dozu(sırasıyla 1.8 ± 1.08 Gy ve 1.44 ± 0.91 Gy, p= 0.037) ES grubunda İSS grubuna kıyasla anlamlı olarak daha yüksek bulunmuştur. Sonuç: ES kullanımı İSS ile karşılaştırıldığında uzamış floro ve işlem süresi, artmış opak yükü ve radyasyon dozu ile ilişkilidir.
Eriyebilen stentlerin prosedür üzerine olan etkilerinin ilaç kaplı stentlerle karşılaştırılması
Keywords: Coronary Artery Disease; Percutaneous Coronary Intervention; Koroner Arter Hastalığı; Perkütan Koroner Girişim